NATIONAL MINORITIES: IVIL INTEGRATION IN GEORGIA - SVANIDZE, Guram (CENTRAL ASIA AND THE CAUCASUS, 2007)
The political and legislative communities long ignored the problem of civil integration of national minorities for the simple reason that the nation had had no time to overcome so-called ethnonational thinking. Its apologists regard minorities as part of an ethno-nation with a statehood of its own, or as an ethno-nation living in a state where it forms a numerically small group with no statehood at all. In this way, statehood and an ethno-national community were considered identical to the extent that the terms could hardly be separated.1The doctrine was equally accepted by the titular and non-titular ethnoses. Its extreme manifestation took the form of ethno-egotism and a “feverish ethnic consciousness;” and general civic principles were pushed aside for the sake of egotistical group interests. The most extreme interpretations of ethno-nationalism result in regimes that tend, on the one hand, toward latent or even obvious ethnic purges. On the other, such manifestations urge national minorities to demand re-division of territories and force them to shift their loyalty from the country they live in to their historical homeland. The non-dominating ethnoses tend to suspect the state of favoring the dominant group at the expense of the rest. On the other hand, the dominant ethnic group suspects the ethnic minorities of ethnic egotism, etc. Ethnic nationalism has already caused segmentation of Georgian society, which constitutes a mêlée of ethnic communities that are diverse but unable to find unity. This created a paradox: part of the Georgian educational infrastructure serves the minorities; there are minorities-oriented media that manage to keep afloat; and there is freedom of communication with the historical homeland. This never led, and could not lead, to integration, instead it deepened disintegration. Under Soviet power, however, this did not bother anyone. The empire’s Center struck a balance between the population majority and the minorities. It preached proletarian internationalism, an ideology that bestowed the role of a unifying and consolidating force on the Russian nation. The nomenklatura mechanism helped to maintain a balance in state administration and relations among the Soviet nations.The balancing factors disappeared along with the Soviet Union to allow ethnocratic trends to promptly move to the fore. Under President Gamsakhurdia, the institutions of statehood were destroyed to please ethnocracy, while state interests deteriorated into narrow sub-ethnic interests. The idea of civic awareness died along with the status of Soviet citizen, while the political vocabulary acquired new tags: “masters,” who belonged to the titular nation, and “guests,” which implied the national minorities